(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Autism is associated with delayed verbal behavior and behavior analysis has allowed the development of Technologies for language teaching. This research aimed to perform a systematic review of the literature on verbal behavior with autistic in TAVB journal. The survey was conducted from 1982 to 2013 with the autism keyword. Were found 136 articles, 39 selected and analyzed for goals, input repertoire, teaching structures, age, year of publication and results. The results showed that most studies taught mand and echoic for individuals aged between three and six years, discrete trial teaching with a single operating per session, and most participants acquired the operating target. There was dearth of research with older children, adolescents and adults, people with autism lack of verbal repertoire and studies with multiple exemplar instruction.